Expert understandings of supervision as a means to strengthen the social service workforce: results from a global Delphi study. Issue 3 (4th May 2018) - Akesson, Bree; Canavera, Mark
ABSTRACT: Learning on how effective social work supervision can strengthen the social service workforce is especially limited in low- and middle-income countries. To address this gap, this paper draws from a global study examining practices and approaches to effectively strengthen the social service workforce. Using a Delphi consensus methodology, the study provided a highly structured means to distil key lessons learned by experts across a range of practice and geographical settings. Over three phases, 43 global experts identified and rated the most effective practices and approaches to strengthen the social service workforce. The findings specific to supervision indicate that most experts strongly agree that access to quality supervision is important. There is also agreement related to the ways in which supervision should be carried out including: individual and group supervision, roleplaying, constructive feedback on practice, and flexibility in the supervisor–supervisee relationship. However, there is still indecision as to whether supervision should be non-hierarchical and egalitarian or, alternatively, directive and regulative. Finally, there was disagreement as to whether supervision should be incentivized. The diversity of participants' examples suggests that the concept of 'supervision' is likely to be subject to highly localized variations that will challenge attempts at creating universally applicable paradigms.